(untitled) (United States, 2010)
In 1906, Teddy Roosevelt created the nation's first National Monument destination. The purpose was to preserve all of America's significant pieces of history. Now viewers can take a journey through the ecology, geology, and beauty of the Great Plains, the geologic West, and the historic South in an adventure never to be forgotten.
Keywords: National monuments,Di tích quốc gia; United States,Hoa Kỳ